PENEGAKAN HUKUM TINDAK PIDANA OLEH BADAN PENGAWAS PEMILU PADA PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR RIAU TAHUN 2018 - Dinda Anggun Komala Citra; Mexsasai Indra; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Elections are the main means of realizing democracy in a country. The substance of the election isthe voice of the people to form representative institutions and government as state administrators. In theprocess of organizing the elections in 2018 in Riau Province there were still many violations of electioncrimes. The formulation of the problem in this study (i) How is the enforcement of criminal acts by theElection Supervisory Agency in the election of Governor and Deputy Governor of Riau in 2018 (ii) What arethe obstacles and efforts to overcome criminal law enforcement by the Election Supervisory Board in theelection of Riau Governor and Deputy Governor in 2018.This type of research can be classified as sociological, because it is based on how to obtain it fromprimary data sources, namely data obtained directly from the main source. This research was conducted atthe Election Supervisory Body of Riau Province, while the population and sample are all parties related tothe problems examined in this study, data sources used primary data, secondary data, and tertiary data,data collection techniques in this study with interviews , observation and literature study.From the results of the research it can be concluded that Law Enforcement of criminal acts by theElection Supervisory Board in the 2018 Governor and Deputy Governor Election has not run optimallybecause there are still frauds committed by the community and there is no Bawaslu authority in attemptingto call the alleged / reported parties in the process information request and lack of expertise of the RiauProvincial Bawaslu staff in the process of taking information or in the process of extracting informationfrom reporters, witnesses and suspects or reported and short handling times is one of the obstacles in theviolation handling process so that the process has not fulfilled enough strong to determine a violation whilethe handling of violations has almost expired. So that the role of Riau Provincial Election Supervisory Bodycannot work optimally in carrying out its duties and functions in supervising the implementation of regionalhead elections, so that there are still cases of electoral crimes that have not been resolved completely in theelection of Governor and Deputy Governor of Riau in 2018.Keywords: Law Enforcement - Bawaslu - Criminal Act on Election.